Why doesn't conventional IVF work in the horse? The equine oviduct as a microenvironment for capacitation/fertilization. Issue 6 (December 2016) - Leemans, Bart; Gadella, Bart M; Stout, Tom A E; De Schauwer, Catharina; Nelis, Hilde; Hoogewijs, Maarten; Van Soom, Ann
Abstract : In contrast to man and many other mammalian species, conventional in vitro fertilization (IVF) with horse gametes is not reliably successful. The apparent inability of stallion spermatozoa to penetrate the zona pellucida in vitro is most likely due to incomplete activation of spermatozoa (capacitation) because of inadequate capacitating or fertilizing media. In vivo, the oviduct and its secretions provide a microenvironment that does reliably support and regulate interaction between the gametes. This review focuses on equine sperm–oviduct interaction. Equine sperm–oviduct binding appears to be more complex than the presumed species-specific calcium-dependent lectin binding phenomenon; unfortunately, the nature of the interaction is not understood. Various capacitation-related events are induced to regulate sperm release from the oviduct epithelium and most data suggest that exposure to oviduct secretions triggers sperm capacitation in vivo . However, only limited information is available about equine oviduct secreted factors, and few have been identified. Another aspect of equine oviduct physiology relevant to capacitation is acid–base balance. In vitro, it has been demonstrated that stallion spermatozoa show tail-associated protein tyrosine phosphorylation after binding to oviduct epithelial cells containing alkaline secretory granules. In response to alkaline follicular fluid preparations (pH 7.9), stallion spermatozoa also show tail-associated protein tyrosine phosphorylation, hyperactivated motility and (limited) release from oviduct epithelial binding. However, these 'capacitating conditions' are not able to induce the acrosome reaction and fertilization. In conclusion, developing a defined capacitating medium to support successful equine IVF will depend on identifying as yet uncharacterized capacitation triggers present in the oviduct.